Young doctors wanted - but how many? Current data on the number of aspiring specialist doctors in orthopedics and trauma surgery in Germany - Muenzberg, Matthias; Sotow, Barbara; Hoffmann, Reinhard; Kladny, Bernd; Stange, Richard; Mutschler, Manuel; Perl, Mario (Unfallchirurg, 2017)
There is an ongoing discussion about demographic change, a possible lack of young doctors and its impact on the healthcare system in Germany. Up to now, no valid data has been available on the exact numbers of residents in orthopedics and trauma surgery. Therefore, the aim of this study was to determine the actual number of residents in Germany in 2013/2014. We generated a database with all eligible providers of postgraduate training in orthopedics and trauma surgery in Germany. All of these were asked to fill out a questionnaire about the number of trainees, their gender and year of training. We achieved an 80% response rate (1509 questionnaires). Within these institutions, 4310 residents are trained. For Germany, this means an estimated number of about 5300 residents in the year 2013/2014. Ninety percent of postgraduate training is performed within a hospital and one-third of the residents are female. Looking at the expected number of doctors who will retire within the next five years, there seems to be enough young doctors to fill the gap. However, by 2040, an increased demand for othopedic and trauma surgeons is experted. Thus, we recommend centrally analyzing and coordinating the demand of residents in orthopedics and trauma surgery in Germany.
Keywords: Demand analysis; Residents; Post-graduate education; Orthopedics; Trauma surgery